2008
DOI: 10.1186/1471-2164-9-538
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the cytochrome P450s, CYP6P3 and CYP6M2 are significantly elevated in multiple pyrethroid resistant populations of Anopheles gambiae s.s. from Southern Benin and Nigeria

Abstract: Background: Insecticide resistance in Anopheles mosquitoes is threatening the success of malaria control programmes. This is particularly true in Benin where pyrethroid resistance has been linked to the failure of insecticide treated bed nets. The role of mutations in the insecticide target sites in conferring resistance has been clearly established. In this study, the contribution of other potential resistance mechanisms was investigated in Anopheles gambiae s.s. from a number of localities in Southern Benin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
289
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(306 citation statements)
references
References 41 publications
10
289
4
Order By: Relevance
“…The gene CYP6M2 was chosen for quantitative real-time PCR (qPCR) and recombinant proteinbased validation. Selection was based in part on our ability to express this class of protein in recombinant Escherichia coli systems and previous association with insecticide, although not DDT, resistance (12,16,18). The other P450 significantly overexpressed in the DDT-resistant group, CYP9L1, was not taken forward for candidate validation because only one of the four CYP9L1 gene probes reached significance and this probe could potentially crosshybridize with two other P450s, AGAP012293 and AGAP012294.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene CYP6M2 was chosen for quantitative real-time PCR (qPCR) and recombinant proteinbased validation. Selection was based in part on our ability to express this class of protein in recombinant Escherichia coli systems and previous association with insecticide, although not DDT, resistance (12,16,18). The other P450 significantly overexpressed in the DDT-resistant group, CYP9L1, was not taken forward for candidate validation because only one of the four CYP9L1 gene probes reached significance and this probe could potentially crosshybridize with two other P450s, AGAP012293 and AGAP012294.…”
Section: Resultsmentioning
confidence: 99%
“…Mosquitoes were defined as resistant if they could survive a 6-h exposure to 4% DDT and a subsequent 24-h holding period. A whole-genome microarray analysis revealed that one of the most consistently overexpressed probe sets in DDT-resistant samples encoded for CYP6M2, an enzyme previously implicated in pyrethroid resistance in A. gambiae (12,16,18). Functional validation confirmed that this enzyme can metabolize both DDT and pyrethroid insecticides.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In whole genome microarray studies of pyrethroid resistant mosquitoes, members of the cytochrome P450 class of metabolic enzymes are frequently up-regulated (Djouaka et al, 2008;Mitchell et al, 2012;Muller et al, 2008;Wondji et al, 2009) suggestive of a predominant role in the resistance phenotype. Confirmatory evidence of a direct role in resistance must come from in vitro metabolism of insecticides with heterologously expressed CYP450, and for a limited number of 4 CYP450s this evidence has been attained (Chiu et al, 2008;Mitchell et al, 2012;Muller et al, 2008;Stevenson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…High expression of P450s has been linked to insecticide resistance in Drosophila (Sundseth et al 1990) and An. gambiae (Müller et al 2007, Djouaka et al 2008). …”
Section: Resultsmentioning
confidence: 99%